Rethinking the Paradigm of Islamic Banking: Integrated of Commercial and Social Oriented - Aisyah, Siti; Ismail, Nurizal; Sulaiman, Ibrahim Fahad; Cahyo, Eko Nur; Sup, Devid Frastiawan Amir (AL-IKTISAB: Journal of Islamic Economic Law, 2022)
••• English ••• The recent appraisal of Islamic Banking and Finance (IBF) development has focused on the interest based banking system. Banks role and function have been retained to create sharia compliant instruments to replace conventional banks interest based instruments. Another issue is the objective of Islamic banking to contribute to social obligation despite profit maximization. In this context, IBF institutions have been involved in debt financing oriented transactions such as murabahah instead of musyarakah and mudharabah, as they are more profitable. This research attempts to clarify Islamic banking's objective derived from Muslim scholars views and how it complies with sharia. Thus, it is necessary to rethink the paradigm of IBF that is in line with pure Islamic economics, whereas conventional banking has been shifting toward social banking. The methodology used is qualitative-descriptive-literature. The result is, several applied integrated models in IBFs, such as Social Islamic Bank Limited (SIBL), have offered Mudaraba Waqf Cash Deposit Account (MWCDA). Then sadaqa house is provided by Bank Islam Malaysia Berhad (BIMB), an integrated institution model in which Islamic banking can cooperate with other Islamic social finance such as waqf institutions in Indonesia. Finally, the research finding argues that Islamic banking's paradigm is to promote the ummah's maslahat by integrating commercial and social aspects into its operational and objective. ••• Indonesian ••• Penilaian perkembangan Islamic Banking and Finance (IBF) baru-baru ini berfokus pada sistem perbankan berbasis bunga. Peran dan fungsi bank tetap dipertahankan untuk menciptakan instrumen yang sesuai dengan syariah untuk menggantikan instrumen berbasis bunga bank konvensional. Isu lain adalah tujuan perbankan syariah untuk berkontribusi pada kewajiban sosial selain juga keuntungan maksimal. Dalam konteks ini, lembaga IBF telah terlibat dalam transaksi yang berorientasi pembiayaan hutang seperti murabahah daripada musyarakah dan mudharabah, karena lebih menguntungkan. Penelitian ini mencoba mengklarifikasi tujuan perbankan syariah yang berasal dari pandangan cendekiawan Muslim dan bagaimana kepatuhannya terhadap syariah. Dengan demikian, perlu dipikirkan kembali paradigma IBF yang sejalan dengan ekonomi Islam murni, padahal perbankan konvensional sudah bergeser ke arah social banking. Metodologi yang digunakan adalah kualitatif-deskriptif-literatur. Hasilnya, beberapa model terintegrasi yang diterapkan di IBF, seperti Social Islamic Bank Limited (SIBL), telah menawarkan Mudharabah Waqf Cash Deposit Account (MWCDA). Kemudian, rumah sedekah disediakan oleh Bank Islam Malaysia Berhad (BIMB), sebuah model lembaga terpadu dimana perbankan syariah dapat bekerja sama dengan keuangan sosial Islam lainnya seperti lembaga wakaf di Indonesia. Akhirnya, temuan penelitian ini berpendapat bahwa paradigma perbankan syariah adalah mempromosikan kemaslahatan umat dengan mengintegrasikan aspek komersial dan sosial ke dalam operasional dan tujuannya.